"Build a friendship with them": The discourse of "at‐risk" as a barrier to relationship building between young people who trade sex and social workers. Issue 4 (23rd March 2017) - Abel, Gillian; Wahab, Stéphanie
Abstract: Young people in statutory care and protection interact with social workers, who hold potential to provide a supportive adult role in their lives. Many however, run away at an early age and end up on the street trading sex for money or other favours. There is potential to improve outcomes for young people in care if the relationship between young people and their social workers is better addressed. This paper uses data from a qualitative study of 14 young people who traded sex and who had experienced interactions with social workers. A thematic analysis identified three themes: the rigidity of social work practice; contesting the family situation; and resisting the at‐risk label. We argue that to have any impact on outcomes for young people in care, social workers need to prioritise relationship‐building above the need to conform to organizational protocols and guidelines. Such guidelines assist the social worker in assessing whether family situations pose high risk for a young person, but the "at‐risk" label is contested by young people, which results in a lack of trust and a barrier to relationship building.